(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The pyroclastic sequences of the south—eastern part of the Island of Ischia (southern Italy) have been studied from a stratigraphic and sedimentological view point.